Quantification of Subsurface Damage in a Brittle Insulating Ceramic by Three-Dimensional Focused Ion Beam Tomography - O'KELLY, KEVIN (My University, 2011)
In this study, we present a fully automated method to investigate and reconstruct the three-dimensional crack structure beneath an indent in a highly insulating material. This work concentrates on issues arising from a long automatic acquisition process, the insulating nature of the specimen, and the introduction of minimal damage to the original cracks resulting from indentation.
PUBLISHED
Keywords: Materials Science; focused ion beam (FIB) microscopy; Nanoscience & Materials